2021
DOI: 10.1002/phar.2649
|View full text |Cite
|
Sign up to set email alerts
|

Role of maternal COVID‐19 vaccination in providing immunological protection to the newborn

Abstract: Pregnant and postpartum individuals are known to have an elevated risk of severe COVID‐19 compared with their non‐pregnant counterparts. Vaccination is the most important intervention to protect these populations from COVID‐19‐related morbidity and mortality. An added benefit of maternal COVID‐19 vaccination is transfer of maternal immunity to newborns and infants, for whom a vaccine is not (yet) approved. Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2)‐specific binding and neutralizing antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Thus far, there is no evidence to suggest that a vaccine against SARS-CoV-2 is harmful to either lactating women or breastfed infants. Many international health organizations, including the Center for Disease Control and Prevention in the US, the Society for Maternal-Fetal Medicine, Gynecologists of Canada, and the American College of Obstetricians and Gynecologists, have recommended the administration of vaccines to pregnant and lactating individuals [16] . The WHO also suggested that pregnant women should discuss with their healthcare provider and obtain a vaccine when the benefits of vaccination outweigh the potential risks.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, there is no evidence to suggest that a vaccine against SARS-CoV-2 is harmful to either lactating women or breastfed infants. Many international health organizations, including the Center for Disease Control and Prevention in the US, the Society for Maternal-Fetal Medicine, Gynecologists of Canada, and the American College of Obstetricians and Gynecologists, have recommended the administration of vaccines to pregnant and lactating individuals [16] . The WHO also suggested that pregnant women should discuss with their healthcare provider and obtain a vaccine when the benefits of vaccination outweigh the potential risks.…”
Section: Introductionmentioning
confidence: 99%
“…For example, local and national health campaigns can provide real-time access of pregnant people and their health care clinicians to the growing scientific evidence demonstrating transplacental and breastmilk antibody transfer following COVID-19 vaccination. 4 , 5 , 6 It is also important to continue research maintaining vaccination in pregnancy registries and publish data on long-term health outcomes of vaccinated pregnant people and their infants. The limitations of this study include low representation of racial groups other than Black and White, and the results may not be representative of other US regions, and a cross-sectional survey design with assessment of attitudes toward COVID-19 vaccination only once during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the negative effect of this infection on pregnancy, considerable support to pregnant patients comes from the implementation of the vaccination campaign. The American College of Obstetricians and Gynecologists (ACOG), the Society for Maternal-Fetal Medicine, the Centers for Disease Control and Prevention (CDC), and the Italian Society Of Gynecology and Obstetrics (SIGO) encourage SARS-CoV-2 vaccination in pregnancy ( ACOG, 2018 ; CDC, 2021 ; Sigo Position Paper, 2021 ; European Center for Disease Prevention and Control, 2020 ), which also provides an immunological protection for the newborn ( Jorgensen et al, 2022 ). In fact, pregnant women generate robust humoral immunity after the mRNA anti SARS-CoV2 vaccination ( Gray et al, 2021 ; Shimabukuro et al, 2021 ).…”
Section: Pregnancy Outcomes After Sars-cov-2 Infectionmentioning
confidence: 99%
“…SARS-CoV-2 specific antibodies are present in both maternal and cord blood, suggesting that antibodies elicited by SARS-CoV-2 immunization cross the placenta ( Beharier et al, 2021 ; Collier et al, 2021 ; Gray et al, 2021 ; Mithal et al, 2021 ). Both spike (S) and receptor binding domain (RBD) IgG antibodies as well as neutralizing antibodies are transplacentally transferred to the newborns, suggesting vaccines as the most important intervention to protect pregnant and breastfeeding women and their offspring from the infection ( Jorgensen et al, 2022 ). To date, one of the most debating issues is to determine the most appropriate timing to assure an effective protection for this dyad.…”
Section: Pregnancy Outcomes After Sars-cov-2 Infectionmentioning
confidence: 99%